Evaluation of an active rehabilitation program for concussion management in children and adolescents. (6th December 2017) - Dobney, Danielle M.; Grilli, Lisa; Kocilowicz, Helen; Beaulieu, Christine; Straub, Meghan; Friedman, Debbie; Gagnon, Isabelle
ABSTRACT: Objective : To estimate the extent to which post-concussion symptoms were influenced by participation in an Active Rehabilitation (AR) program (aerobic exercise, coordination drills, visualization and education) for children and adolescents who are slow to recover from concussion. A secondary exploratory objective included examining the influence of sex on symptom evolution. Methods : Analysis of prospectively collected data was performed on 277 youth who initiated an AR program, between three and four weeks post-injury at a Concussion Clinic in a tertiary care paediatric teaching hospital. Main outcome measure : Post-concussion symptom scale (PCSS) from Sport Concussion Assessment Tool-3 (SCAT 3). Results : Children and adolescents participating in an active rehabilitation program displayed improved post-concussion symptom severity at follow-up (median = 9.5) compared to pre-intervention (median = 18) ( p < .05). Patients demonstrated improved physical, cognitive, emotional and sleep-related post-concussion symptoms ( p < .05). Female sex was associated with an increased post-concussion symptom severity at follow-up. Conclusions : Youth experiencing persisting symptoms three to four weeks post-concussion demonstrated improved post-concussion symptoms scores (physical, cognitive, emotional and sleep related) with participation in an active rehabilitation program.